Synthesis of nano-fluorohydroxyapatite thin films by sol-gel method - Darroudi, Majid; Hossein, Eshtiagh-Hosseini; Housaindokht, Mohammad Reza; Youssefi, Abbas (Malaysian Journal of Science, 2010)
It is realized that the surface of biomedical metallic implants covered by fluorohydroxyapatite, [Ca10(PO4)6(0H, F)] (FHA) can create bioactivity of the implant and shorten healing time. In this work FHA, in the form of powders and of thin films on titanium substrates, were synthesized by sol-gel spin coating method, using calcium nitrate tetrahydrate (Ca(NO3)2).4H20, phosphorous pentoxide (P205) and ammonium fluoride (NH4F) to provide Ca-precursor, P-precursor and fluorine reagent, respectively. The FHA powders were calcined and thin films were fired at temperatures ranging from 500-800Â°C. The constituent of both powders and thin films were confirmed as FHA using X-ray diffraction (XRD) and Fourier transform Infrared spectroscopy (FTIR). The thermal stability of FHA powders was studied by differential thermal analysis (DTA). The optimized calcination and firing temperature was 600 Â°C. Transmission electron microscopy (TEM) results with Debye-Scherrer equation gave the size of the FHA particles in nano-scale range. The films were found to be quite uniform and dense by SEM.